Use of social media in crisis management: A survey - Saroj A.; Pal S. (My University, 2025)
Emergency situations arising out of natural disasters like tsunami, earthquakes, floods, hurricanes or man-made ones like terror strikes, riots, accidents, etc. cause tremendous social and economic loss and badly affect the poor in low-income economies, in particular. In this paper, we attempt to see and analyze the relationship between emergencies and online social media, especially Twitter, Facebook, and Youtube. Specifically, we look at three important issues. First, we try to see the effect of occurrence of emergencies on social media. Second, when there is a sudden surge of posts in social media due to the occurrence, how that deluge of data can be effectively extracted and processed to create situational awareness and minimize the damage due to the disaster. Third, how different social media posts can help different government and other agencies to get prepared and to take necessary steps to manage emergencies in order to minimize the loss. In this survey, the papers centered around emergencies and its effect on social media and different organizations related to crisis management are considered that are published in the past decade. © 2020